Relationships Among the Rootstock, Crop Load, and Sugar Hormone Signaling of Apple Tree, and Their Effects on Biennial Bearing - Kviklys, Darius; Samuolienė, Giedrė (Frontiers in Plant Science, 2020)
Adjustable crop load primarily involves bud manipulation, and usually switches from vegetative to reproductive buds. While this switch is not fully understood, it is still controlled by the ratio of hormones, which promote or inhibit bud formation. To determine the reasons for biennial bearing, the effect of apple rootstock, scion cultivar, crop load, as well as metabolic changes of endogenous phytohormones (zeatin, jasmonic acid, indole-3 acetic acid (IAA), abscisic acid (ABA), and gibberellins 1, 3 and 7 (GAs)), and soluble sugars (glucose, fructose, and sorbitol) were evaluated, and their connections with return bloom and yield of apple tree buds were analyzed. Cultivars ʹLigolʹ and ʹAuksisʹ were tested on five rootstocks contrasting in induced vigor: semi-dwarfing M.26; dwarfing M.9, B.396, and P 67; and super-dwarfing P 22. Crop load levels were adjusted before flowering, leaving 75, 113, and 150 fruits per tree. Principal component analysis (PCA) scatter plot of the metabolic response of phytohormones and sugars indicated that the effect of the semi-dwarfing M.26 rootstock was significantly different from that of the dwarfing M.9 and P 67, as well as the super-dwarfing P 22 rootstocks in both varieties. The most intensive crop load (150 fruits per tree) produced a significantly different response compared to less intensive crop loads (113 and 75) in both varieties. In contrast to soluble sugar accumulation, increased crop load resulted in an increased accumulation of phytohormones, except for ABA. Dwarfing rootstocks M.9, B.396, and P 67, as well as super-dwarf P 22 produced an altered accumulation of promoter phytohormones, while the more vigorous semi-dwarfing M.26 rootstock induced a higher content of glucose and inhibitory phytohormones, by increasing content of IAA, ABA, and GAs. The most significant decrease in return bloom resulted from the highest crop load in ʹAuksisʹ grafted on M.9 and P 22 rootstocks. Average difference in flower number between crop loads of 75 and 150 fruits per tree in ʹLigolʹ was 68%, while this difference reached 90% for P 22, and 75% for M.9 and M.26 rootstocks. Return bloom was dependent on the previous year’s crop load, cultivar, and rootstock.